Effectiveness of e-module based on guided discovery learning on learning outcomes of high school students - Alysa Luthfiani; Yerimadesi Yerimadesi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
This study aims to analyze the effectiveness of e-module colligative properties of solutions based on guided discovery learning in improving high school student learning outcomes. The research was conducted on class XII students in a public high school space (MAN 1 Padang) with 36 students. The type of research used is quasi-experimental. The research design was a randomized control-group pretest-posttest design, and data analysis used a t-test. The sample was taken by a simple random sampling technique. The level of effectiveness of the e-module is analyzed from the results of the n-gain value. It obtained an n-gain value of 0.71 in the high category. In conclusion, guided discovery learning based on the chemistry e-module effectively improves student learning outcomes with high criteria. Keywords: Effectiveness, E-Module, Guided Discovery Learning, Learning Outcomes.